Expressions for Fučik spectra for sturm‐liouville BVP - Tatjana Garbuza (Mathematical Modelling and Analysis, 2007)
We provide explicit formulas for the Pučik spectra of boundary value problems with the Sturm‐Liouville boundary conditions.